Organizational commitment and its impact on the turn over intentions among employees of the organization - Shahid, Nida; Ahmad, Bashir (Journal of Pakistan Psychiatric Society, 2021)
Objective: The aim of this study is to find out Employee’s organizational commitment and its impact on the turn over intentions among employees of the organization. Design: Descriptive / Exploratory Place and Duration of study: Data collected from March 2019 to May 2019 from doctors and university Teachers of Peshawar. Subjects and method: Study recruited, a sample of 300 subjects that comprised of 150 doctors and 150 university teachers. Sample was drawn through convenient sampling from different hospitals and universities of Peshawar. Allen & Meyer commitment scale and turn over intention scale were used in the study. This study found that commitment has great effect (R=0.624) on turnover but it also highlighted three types of commitment and their effect on turnover. This study was conducted with the hypothesis that Commitment would have a higher effect on the turnover. Results: Results showed that all types of commitment including Affective commitment, Continuous Commitment and Normative commitment had effect on the turnover of doctors and University teachers. Affective Commitment, however was found to be a stronger predictor of turnover among selected hospitals and university employees. Conclusion: To increase the level of commitment among employees, organization should take serious steps to motivate employees by giving them incentives, as well as provide clear job plan, conducive work culture, organizational support, better work environment and supportive supervision.